A case of early gastric cancer with a single giant lymph node metastasis - Masato Yoshikawa; Misaki Tamario; Masayoshi Obatake; Koichi Sato; Shigehiko Yagi; Hiromi Otani; Katsumi Kito (Surgical Case Reports)
Abstract Background Early gastric cancer (EGC) is often associated with lymphatic metastasis, but it is extremely rare to be found as a single giant lymph node. Cancer often becomes more malignant in metastatic lesions than in primary lesions, and retrodifferentiation to the fetal gastrointestinal tract during the metastatic process has been reported in gastric cancer. We report an extremely rare case of EGC with a 13-cm giant lymph node metastasis in which an adenocarcinoma with enteroblastic differentiation and yolk sac tumor-like components was observed. Case presentation The case was a 70-year-old man who visited his local doctor with right hypochondrial pain, which was identified by computed tomography (CT) as a giant mass. Upper endoscopy revealed a 30-mm-sized 0-IIc lesion in the greater curvature of the angular incisure and a 15-mm-sized 0-IIa lesion in the anterior wall of the lower body of the gastric body. Endoscopic biopsy revealed tubular adenocarcinoma in both lesions. The gastric lesion and the giant tumor were clinically regarded as independent lesions (gastrointestinal stromal tumor, [GIST], and EGCs), and distal gastrectomy and D1 + dissection were performed to comprehensively treat all lesions. Pathological examination revealed that the giant tumor was tubular adenocarcinoma with an intestinal phenotype and was considered a lymph node metastasis of EGCs. To exclude the possibility of metastasis of adenocarcinoma other than EGCs, postoperative positron emission tomography-computed tomography (PET-CT) and colonoscopy were performed; however, no primary site other than the stomach was found. Metastatic lymph nodes have an increased degree of atypia compared with the primary tumor, and yolk sac tumor-like carcinoma morphology was observed along with α-fetoprotein (AFP) and Spalt-like 4 (SALL4) expression in this case. It was considered that retrodifferentiation to a fetal phenotype occurred during the metastatic process. Liver metastasis occurred 6 months after surgery, and chemotherapy is currently being introduced. Conclusions We experienced a case of EGC with a single giant lymph node metastasis. Retrodifferentiation to the fetal gastrointestinal tract during metastasis was speculated to be involved in the formation of giant lymph node metastasis and liver metastasis in this case.